Difficult to Create But Easy to Reject: The Case of ICC Rejection by the AU - Paul S. Masumbe (Britain International for Academic Research (BIAR-Publisher), 2023)
Even though the creation of the International Criminal Court (ICC) was greatly welcomed by African states, the prosecution of mostly African state officials by the Court since its creation has sparked animosity between the ICC and the African Union (AU), leading to the rejection of the Court’s perceived bias activities in the Africa continent. While it is legally justifiable for the Prosecutor of the ICC to prosecute African state officials, partly because the Court has jurisdiction to entertain crimes committed by African state officials and also because 33 states in Africa have ratified the Rome Statute, it is legitimately inappropriate for the Prosecutor of the ICC to prosecute mostly African state officials given the fact that the ICC has jurisdiction to entertain similar crimes committed in other continents of the world. Accordingly, not all cases and situation prosecuted by the Office of the Prosecutor (OTP) of the ICC that are legally justifiable are legitimate. After discussing the creation of the ICC, this article will examine whether it was legally and legitimately justifiable for the Prosecutor of the ICC to target mostly African state officials for almost two decades and whether the creation of the African Criminal Court (ACC) is the African panacea as a consequence of the alleged bias between the ICC and the AU regarding the prosecution of African state officials.